Vegetation Structure in Artificially Raised Young forests of Tectona grandis in Moist Deciduous Region - Jha, Kaushalendra Kumar (Indian Forester, 2004)
Phytosociological studies were carried out in an age series Teak plantation (1, 5, 11, 18, 24 and 30 years). In these stands average basal area increased with growing age. Density had inconsistent relationship but indicated towards a decrease, as the plantations grew older. In the case of shrubs also density had the same trend. Association of certain species with original vegetation was retained while few new ones got introduced during the course of time. Seasonal record of herbs indicated that total number of species was highest in rains followed by summer and winter seasons. An interesting finding of this study was that higher number of species was found in artificially regenerated Teak plantations in comparison to the original natural Sal forests.